2(x+4)-2=4x-(3x+2)

Simple and best practice solution for 2(x+4)-2=4x-(3x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+4)-2=4x-(3x+2) equation:


Simplifying
2(x + 4) + -2 = 4x + -1(3x + 2)

Reorder the terms:
2(4 + x) + -2 = 4x + -1(3x + 2)
(4 * 2 + x * 2) + -2 = 4x + -1(3x + 2)
(8 + 2x) + -2 = 4x + -1(3x + 2)

Reorder the terms:
8 + -2 + 2x = 4x + -1(3x + 2)

Combine like terms: 8 + -2 = 6
6 + 2x = 4x + -1(3x + 2)

Reorder the terms:
6 + 2x = 4x + -1(2 + 3x)
6 + 2x = 4x + (2 * -1 + 3x * -1)
6 + 2x = 4x + (-2 + -3x)

Reorder the terms:
6 + 2x = -2 + 4x + -3x

Combine like terms: 4x + -3x = 1x
6 + 2x = -2 + 1x

Solving
6 + 2x = -2 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
6 + 2x + -1x = -2 + 1x + -1x

Combine like terms: 2x + -1x = 1x
6 + 1x = -2 + 1x + -1x

Combine like terms: 1x + -1x = 0
6 + 1x = -2 + 0
6 + 1x = -2

Add '-6' to each side of the equation.
6 + -6 + 1x = -2 + -6

Combine like terms: 6 + -6 = 0
0 + 1x = -2 + -6
1x = -2 + -6

Combine like terms: -2 + -6 = -8
1x = -8

Divide each side by '1'.
x = -8

Simplifying
x = -8

See similar equations:

| 13x-9=-2(-4x-3) | | 3/4m=75 | | 20x-7=-3(-4x-3) | | 21+3c-7(2-3c)=4(c-5)3c+27 | | (8x^3)-(14y)+(12x)=0 | | 1/14b=-2.39 | | 0.37=ln(-2.5k) | | -0.994=ln(-2.5k) | | lnx=2.25 | | 6cos^2x-17cosx+7=0 | | 9=1/2a | | -3x^2+14x+49=-42 | | 2e^5x=14 | | -3x^2+14x+49=42 | | 6.1=x+(-7.3) | | 6cos^2x-17x+7=0 | | 7(x+7)=-11-3x | | -6(1-8k)=-20 | | 5-(-7*-4)=-33 | | 3y=7x-1 | | -28=12+2z | | (2-x).5=10 | | ln(1+x)-lnx=.25 | | -5x-10=5x | | 4(6x+7)=-40+7x | | 6x+15=9x+13-5x | | 16+4r=8(2+7r) | | 8y+6=3x | | 16x^2+3x+1=0 | | x+(x+1)=380 | | 8-6x-x^2=6+x | | -3h-5=-3h |

Equations solver categories